PENGEMBANGAN DIGITAL LIBRARY MENGGUNAKAN SENAYAN LIBRARY MANAGEMENT SYSTEM (SLIMS) DI LABORATORIUM MULTIMEDIA JURUSAN KTP FIP UNP - Nofri Hendri; Septriyan Anugrah (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
This research is a research development known as research and development (R & D). The development model used is a development model proposed by Borg and Gall modified. The product of this development was assessed by 2 media experts and practicable test of 20 members of FIP UNP library. Instruments used in this research are documentation, assessment format and questionnaire to see the ease for the subject try using digital library product. The results of this research indicate that the digital library product that has been developed to get the category of Excellent from both media expert validators. Similarly, the results of practicality test against library members obtained the assessment with the category Very Good with the acquisition value of 4.55. Thus the results showed that digital library products using the application Senayan Library Management System (SLiMS) Version 8 in the FIP UNP Library that has been developed valid and practical to use.Keywords : Digital Library, Senayan Library Managemen System (SLiMS)